al-Lughah al-‘Arabīyah wa-Mutaṭallabāt Tadrīsihā al-Ijtimā‘īyah wa-al-Thaqāfīyah: Qirā’ah Taḥlīlīyah li-al-Lughah fī al-Siyāq al-Ma‘rifī li-Sūsiyūlūjīyat al-Lughah wa-al-Ta‘allum - Malika Araour (Universitas Negeri Jakarta, 2018)
The problem of this study revolves around the most important tool in building human knowledge and the most important means of understanding and friction among the members of the society to practice life or knowledge in all fields of social life and to meet their needs and determine how to satisfy them. The question of this study is based: how to link Arabic language education to its social and cultural dimensions? The importance of the topic lies in uncovering the profound historical and social links of the language to achieve an integrated dynamic of social and cultural structure that will add to the teaching of the Arabic language associated with the teaching of Arabic culture. This research was based on a descriptive approach. The study reached the following results: the need to learn the Arabic language interspersed with the culture of society, and linking the linguistic studies of the Arabic language to social anthropology studies.